2015
DOI: 10.1021/acs.jpclett.5b01806
|View full text |Cite
|
Sign up to set email alerts
|

Strain Tuning of Ferroelectric Polarization in Hybrid Organic Inorganic Perovskite Compounds

Abstract: Metal-organic frameworks (MOFs) are hybrid crystalline compounds comprised of an extended ordered network made up of organic molecules, organic linkers and metal cations. In particular, MOFs with the same topology as inorganic perovskites have been shown to possess interesting properties, e.g., coexistence of ferroelectric and magnetic ordering. Using first-principles density functional theory, we have investigated the effect of strain on the compounds C(NH2)3Cr(HCOO)3 and (CH3CH2NH3)Mn(HCOO)3. Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 58 publications
(94 reference statements)
1
53
0
Order By: Relevance
“…The known formates have been extensively studied in a broad temperature range, and these studies showed that majority of them undergo phase transitions associated with orientational ordering of organic cations located in the cavities of the framework . Pressure is another thermodynamic parameter that can help to better understand structure–property relationship in this class of compounds . For instance, it has been shown that application of pressure may lead to enhancement of ferroelectric properties or its suppression .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The known formates have been extensively studied in a broad temperature range, and these studies showed that majority of them undergo phase transitions associated with orientational ordering of organic cations located in the cavities of the framework . Pressure is another thermodynamic parameter that can help to better understand structure–property relationship in this class of compounds . For instance, it has been shown that application of pressure may lead to enhancement of ferroelectric properties or its suppression .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been shown that application of pressure may lead to enhancement of ferroelectric properties or its suppression . Furthermore, application of pressure may lead to discovery of novel polymorphs that are not thermodynamically stable at ambient conditions . We have decided, therefore, to study high‐pressure behaviour of recently discovered acetamidinium manganese formate ([CH 3 C(NH 2 ) 2 ][Mn(HCOO) 3 ], AceMn), using Raman spectroscopy because this method is well‐known to be a very valuable tool in high‐pressure studies due to its sensitivity to changes in dynamics and structure of molecular units …”
Section: Introductionmentioning
confidence: 99%
“…They are isostructural and crystallize at room temperature in the non‐centrosymmetric Pna 2 1 space group with ordered EtA + cations. Because the structure is polar, these compounds are possible ferroelectrics and EtAMn can be regarded as a multiferroic material . Interestingly, theoretical considerations showed that the ferroelectric polarization can be strongly increased by applying compressive strain .…”
Section: Introductionmentioning
confidence: 99%
“…Metal-formate frameworks (MFFs) have attracted considerable attention in the past decade due to their rich physical properties which include magnetism [1,2,3], ferroelectricity [3,4,5,6], negative linear compressibility [7], mechanical properties [8,9,10,11], and dielectricity [12,13]. Very recently, a few research groups have discovered that these MFFs can also exhibit large negative thermal expansion (NTE) properties [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%